Specificity of 2 peripartum blood markers for early-lactation acute uterine inflammation in pasture-fed, seasonal-calving dairy cows - O.K. Spaans; J.R. Roche; C.R. Burke; C.V.C. Phyn; S. McDougall; C.B. Reed; B. Kuhn-Sherlock; A. Hickey; A. Heiser; M.A. Crookenden (JDS Communications)
A delayed recovery of the reproductive tract from natural inflammatory processes associated with postpartum involution will compromise further reproductive function. Following a literature review, we selected serum amyloid A (SAA) and α1-acid glycoprotein (α1-AGP) to assess as potential circulating markers of acute uterine inflammation, as concentrations of these 2 acute phase proteins were reported to be elevated early postpartum in dairy cows with active uterine infection. Convenience serum samples from an induced model of uterine infection were used to measure concentrations of these markers. Infection was induced by infusing either 107 or 109 cfu of Trueperella pyogenes (n = 9 cows each; bacteria group n = 18) or saline as a control (n = 18) into the uterus at 48 d postpartum. Although infection stimulated an increase in uterine polymorphonuclear neutrophils, SAA and α1-AGP concentrations in serum were not different between infusion groups. Cows were subsequently classified into uterine health groups based on the presence of endometritis, with or without the presence of T. pyogenes in uterine culture in response to uterine infusion. Mean SAA concentrations were greater in cows that were either endometritis negative–infection positive (n = 9), endometritis positive–infection negative (n = 5), or endometritis positive–infection positive, compared with the endometritis negative–infection negative (n = 11) cows. There was no difference between uterine health groups for α1-AGP concentrations.